MaterialTool a selection guide of materials and processes for designers - Wroblewski, Andrzej Jan.; Vanka, Suryanarayana (Englewood Cliffs, N.J. Prentice-Hall, 1999)
Details properties of over 600 materials and demonstrates more than 400 processes, such as Abrading and ZigZag Stitching. Includes tutorial and a reference section for books, websites and videos.
Title from disc label.
System requirements: IBM or compatible 386 or better (486 or Pentium preferred); Windows 3.1, Windows 95 or Windows NT; 8MB RAM (16MB recommended); 2X CD-ROM drive or better; 256 colors; 640x480 VGA or better.
Keywords: Building materials -- Software; Manufacturing processes -- Software; Industrial design -- Software